Chest imaging for COVID-19: a single-center comparative results in pediatric patients - Özcan, H Nursun; Özsürekci, Yasemin; Oğuz, Berna; Oygar, Pembe Derin; Gürlevik, Sibel Laçinel; Karakaya, Jale; Tekşam, Özlem; Ceyhan, Mehmet; Haliloğlu, Mithat (The Turkish Journal of Pediatrics, 2022)
Background. Chest computed tomography (CT) appears to be an important radiological modality for the diagnosis of COVID-19 in adults. Studies comparing the findings of such children with those of other viral infections have not been reported either. The aim of this study was to present comparative imaging findings of 75 pediatric COVID-19 patients and four patients with other viral upper respiratory tract infections. We also aimed to demonstrate the possible association between the radiological and laboratory findings in the COVID group. Methods. From 11 March 2020 to 20 June 2020, 79 children (aged < 18 years) were enrolled. COVID-19 was detected by RT-PCR or antibody testing. A plain chest X-ray was obtained from all subjects. Non-contrast chest CT was performed for symptomatic patients. Results. Seventy-five patients had COVID-19 and 4 were infected with other pathogens i.e. adenovirus, rhinovirus, parainfluenza virus B, respiratory syncytial virus. The ages of the patients (36 M, 43 F) ranged from 7 months to 17 years old. The sensitivity of chest X-ray (as compared to RT-PCR) was 10.67% (95 CI%: 4.72 - 19.94%). From 23 chest CT`s five of them were normal and nine of them had only nodules ( < 5mm). The sensitivity of CT was 78.26% (95CI%: 54.30 - 92.54%), false-negative rate was 21.7%. Conclusions. The sensitivity of chest CT was found to be low and any significant correlations could have not been depicted, between the radiological parameters and the presence of lymphopenia. Clinical follow-up combined with corresponding pathogen detection, and chest CT of the symptomatic COVID-19 patients might be a feasible/prompt protocol in children.